2019
DOI: 10.4238/gmr18119
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic diversity in native <i>Genipa</i> <i>americana</i> (Rubiaceae) populations in Sergipe, Brazil

Abstract: Genipap (Genipa americana-Rubiaceae) is native to tropical America, occurring in Brazil in practically all biomes, except in the Pampas. It has socioeconomic importance, mainly due to the use of fruits in the manufacture of sweets and juices besides the medicinal properties of its leaves. We evaluated the genetic diversity of 73 individuals from 15 natural populations in the state of Sergipe using ISSR markers. The choice of areas was made randomly and genetic material was extracted from young leaves. PCR anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…These authors reported that the genetic similarity index (Jaccard index) between individuals was 60.4% on average, while the greatest distance of similarity obtained was observed between individuals (83.6 % ± 0.03), as well as the lowest genetic similarity between individuals (36.5 % ± 0.02). This indicates an intermediate genetic diversity, as found by Cardoso et al (2019) in a study carried out in natural populations of G. americana in the Brazilian state of Sergipe. As previously indicated, differences were found in this study with regard to plant development for the variables of plant height and DBH during the vegetative phase according to the origin.…”
Section: Discussionsupporting
confidence: 54%
“…These authors reported that the genetic similarity index (Jaccard index) between individuals was 60.4% on average, while the greatest distance of similarity obtained was observed between individuals (83.6 % ± 0.03), as well as the lowest genetic similarity between individuals (36.5 % ± 0.02). This indicates an intermediate genetic diversity, as found by Cardoso et al (2019) in a study carried out in natural populations of G. americana in the Brazilian state of Sergipe. As previously indicated, differences were found in this study with regard to plant development for the variables of plant height and DBH during the vegetative phase according to the origin.…”
Section: Discussionsupporting
confidence: 54%
“…Various types of molecular markers have been developed according to their application efficiencies (Nadeem et al 2018). Studies have confirmed that ISSR are abundant and widely distributed throughout plant nuclear genomes (González et al 2007;Ekincialp et al 2019;Nadeem et al 2018) and have been successfully utilized for the assessment of population structure and genetic variation in various crop species (Cardoso et al 2019;Ekincialp et al 2019;Ali et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Foram 21 artigos científicos, um livro, dois capítulos de livro e três publicações técnicas, além de seis dissertações e três teses. Os principais temas abordados foram cultura de tecidos/micropropagação (42,30%) [14][15][16][17][18][19][30][31][32][33]; diversidade genética/biologia molecular (11,53%) [34][35][36]; recursos genéticos (15,38%) [4,12,[37][38][39]; bioativos (11,53%) [20,21,40]; propagação (7,69%) [13,41] e pós-colheita (11,53%) [42][43][44] Os estudos sobre diversidade têm mostrado a necessidade de estabelecer estratégias que permitam a recuperação e o aumento da diversidade genética tanto in situ quanto ex situ. Os resultados da cultura de tecidos têm avançado e a expectativa é ter alguns acessos do BAG mantidos in vitro.…”
Section: Resultsunclassified